Discerning Domestic Space in a Palaeo-Eskimo Structure from Interior Baffin Island - DeGagne, Andrea (My University, 2009)
This thesis explores the potential for using high-resolution distributional analyses in domestic space, to better understand the social realm of Palaeo-Eskimo societies. Lithic debitage distributions from inside and around a single archaeological structure from LdFa-1, a multi-component campsite from Interior Baffin Island, were assessed to determine if patterning in the use of domestic space could be distinguished. Distributions were analyzed with Inverse Distance Weighting (IDW) interpolation, and compared to the dispersal of formal artefacts across the site. Debitage smaller than 5 cm exhibited a single area of activity within a bounded structure, while no further patterning in the use of interior space could be defined. This finding is contrmy to the bilateral distribution of interim space identified by McGhee (1979) from early Palaeo-Eskimo coastal settlements, suggestive of a more relaxed social atmosphere in these inland campsites. However, further investigations with the increased resolution of this study need to be undertaken to understand tile intra-site and inter-regional variation that exists in Palaeo-Eskimo structures. Most importantly, it is hoped that upcoming excavations employ similar high-resolution sampling strategies that maintain the smallest debitage for spatial analysis, so that a body of data necessary for intra-site, domestic analyses can be built up for future investigations at this scale.
Keywords: Anthropology; Anthropology